Ecosystem services and disservices associated with pastoral systems from Patagonia, Argentina –A review - Tittonell, Pablo Adrian; Hara, Sofia Maria; Alvarez, Valeria Esther; Aramayo, Maria Valeria Del Luján; Bruzzone, Octavio Augusto; Easdale, Marcos Horacio; Enriquez, Andrea Soledad; Laborda, Luciana; Trinco, Fabio Daniel; Villagra, Edgar Sebastian; El Mujtar, Veronica Andrea (EDP Sciences, 2022)
Pastoral systems worldwide secure rural livelihoods in the harshest environments on Earth. Their low productivity per area unit or head makes them the subject of much criticism with regard to their environmental impact, particularly in relation to global warming, desertification and land degradation. Such is the case of the traditional pastoral systems of Patagonia, a vast and isolated region where sedentary and mobile pastoralism coexist and contribute to shape landscapes and cultures.We argue that pastoral systems provide a wide range of ecosystem services that may compensate for their negative impact on the environment.We review the scarcely available evidence from Patagonia to identify ecosystem services and disservices associated with pastoralism, and pay special attention to the carbon balance: with C footprints between 10 to 40 kgCO2-eq.kg1 carcass, pastoral systems in dry Patagonia are below or within the range of semi-extensive livestock systems worldwide (35–45CO2-eq. kg1 carcass). To inform development and policy, the assessment of trade-offs and synergies between ecosystem services needs to incorporate the intertwined social and ecological dynamics of complex pastoral systems, along resource regenerative trajectories.